Late‐Onset Multiple Acyl‐CoA Dehydrogenase Deficiency (MADD): A Case Report With a Complex Biochemical Profile - Romain Penicaud; Jean‐Baptiste Ferron; Xavier Valette; Pierrick Bauduin; Maxime Faisant; Manuel Schiff; Alexandre Nguyen; Fanny Fontaine; Stéphane Allouche (JIMD Reports)
ABSTRACT Three clinical entities of multiple acyl‐CoA dehydrogenase deficiency (MADD, OMIM#231680) can be differentiated: two severe neonatal forms and one later‐onset form that can manifest in adulthood. The latter typically presents with muscle‐related symptoms, such as exercise intolerance and muscle weakness, with an increase in all chain‐length acylcarnitine species on the acylcarnitine profile. Here, we report the case of a 33‐year‐old woman who experienced severe psychiatric issues complicated by an eating disorder resulting in a significant malnutrition a few months before presenting with a profound muscle weakness, fatigue, intermittent ptosis, and a major rhabdomyolysis (creatine kinase (CK) > 15 000 IU/L). Biochemical blood tests, including acylcarnitine profile, urinary organic acid analysis, and in vitro beta‐oxidation, were not suggestive of a metabolic disease. Given the absence of an etiology and the worsening health condition of the patient, whole exome sequencing (WES) was performed and revealed two pathogenic variants in the electron transfer flavoprotein dehydrogenase (ETFDH) gene, whose association has not been reported before. Unlike other beta oxidation deficiencies, which have a typical biochemical signature, the diagnosis of MADD was made by genetic analyses, which allowed the introduction of vitamin B2 supplementation and the rapid improvement of symptoms.